Corrosion fatigue behaviour of HFMI-treated butt welds. (April 2021) - Gkatzogiannis, Stefanos; Weinert, Joscha; Engelhardt, Imke; Knoedel, Peter; Ummenhofer, Thomas
Highlights: Investigating influence of corrosion on the efficiency of HFMI. Application of laboratory tests to simulate real marine corrosion conditions. Correlation between laboratory and real conditions based on a previous study. Influence of loading mode taken into consideration. Boundaries of the research set to tackle a practical problem of offshore engineering. Significant increase of fatigue life in corrosive environment. Present first-step investigation clarifies the next steps to be taken. Abstract: The present study reports on the results of a completed research project, which investigated the corrosion fatigue behaviour of weldments made of structural steel S355J2+N treated with the High Frequency Mechanical Impact (HFMI). Main goal has been the estimation of short corrosion on the surface layer (<1 year) on the fatigue strength of uncoated HFMI-treated specimens. Axial and 4-point bending fatigue tests were carried out on uncorroded and corroded butt welds both for the as-welded and HFMI-treated state. Marine corrosion is simulated in the laboratory with exposure in a Salt Spray Chamber (SSC) tests and deposition in Artificial Seawater (ASW). SSC was applied as pre-corrosion means while corrosion in ASW took place simultaneously during fatigue testing of specimens pre-corroded in the same corrosive medium. Extrapolation of the laboratory results to real marine corrosion (RC) is carried out based on findings from an earlier study of the authors, where specimens corroded in the laboratory were compared with reference specimens exposed to the real marine splash zone in the Baltic Sea. Material removal rate, increase of surface roughness and reduction of fatigue life are considered for this comparison. Significant conclusions regarding corrosion fatigue resistance of both as-welded and HFMI-treated specimens are drawn. Assumptions and initial expectations regarding the influence of corrosion on both fatigue crack initiation and crack growth regimes are either confirmed or overthrown. In all investigated cases for thickness reduction up to 0.1 mm, significant increase in fatigue life is achieved through the application of HFMI. Finally, recommendations for future work regarding the clarification of open questions from the present study are presented.